2010
DOI: 10.1007/s12011-010-8772-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary High Molybdenum on the Cell Cycle and Apoptosis of Kidney in Broilers

Abstract: The experiment was conducted with the objective of examining the effects of high molybdenum on the cell cycle and apoptosis of kidney in broilers by the methods of flow cytometry. Three hundred 1-day-old Avian broilers were randomly divided into four groups, and fed on diets as follows: control diet (Mo 13 mg/kg) and high molybdenum diets (Mo 500 mg/kg, high molybdenum group I; Mo 1,000 mg/kg, high molybdenum group II; Mo 1,500 mg/kg, high molybdenum group III) for 6 weeks. The results showed that the relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Additionally, high levels of Mo can result in unregulated expression of Bax, CytC, and Caspase-3, whereas it downregulates Bcl-2 in goat kidney [12]. Mo administration has induced an increase in Bax expression and a decrease in Bcl-2 expression in chicken kidney cells [39]. In this study, Mo and/or Cd treatment resulted in downregulation of Bcl-2 mRNA expression but upregulation of Bak-1 and Caspase-3 mRNA expression in duck spleen tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, high levels of Mo can result in unregulated expression of Bax, CytC, and Caspase-3, whereas it downregulates Bcl-2 in goat kidney [12]. Mo administration has induced an increase in Bax expression and a decrease in Bcl-2 expression in chicken kidney cells [39]. In this study, Mo and/or Cd treatment resulted in downregulation of Bcl-2 mRNA expression but upregulation of Bak-1 and Caspase-3 mRNA expression in duck spleen tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Bax oligomerization is thought to increase the mitochondrial outer membrane permeability, leading the release of apoptotic proteins, like Cyt c into the cytoplasm. Previous research has indicated that Cd induced renal apoptosis by modulating Bax and Bcl-2 expression (Chen et al, 2013), and Mo also increased Bax protein and decreased Bcl-2 protein (Xiao et al, 2011). Smac promotes apoptosis through mediating the interaction between caspases and IAPs (Inhibitor of Apoptosis Proteins).…”
Section: Discussionmentioning
confidence: 99%
“…The literature about MO exposure in laying hens is limited, but previous studies conducted in human and rats indicated that high MO can lead to growth depression, impairment of reproductive performance, and renal failure [24,25,26]. Moreover, it has been indicated that exposure to high levels of MO can result in spleen and kidney toxicity in broilers and ducks [10,27,28,29], which may cause growth retardation and reduction in productive performance. In case of liver damage, blood concentration of ALT and AST, the main aminotransferases involved in the synthesis process of nonessential amino acid, would increase, reflecting impaired hepatic ALT and AST activities [30].…”
Section: Discussionmentioning
confidence: 99%
“…In case of liver damage, blood concentration of ALT and AST, the main aminotransferases involved in the synthesis process of nonessential amino acid, would increase, reflecting impaired hepatic ALT and AST activities [30]. It has been reported that excessive MO may result in morphological and functional changes in the liver, kidney, and spleen [10,27]. Xanthophylls, a subclass of carotenoids, are responsible for egg yolk pigmentation [31].…”
Section: Discussionmentioning
confidence: 99%